EXTREMISM CONTENT IN THE TEXTBOOK HISTORY OF ISLAMIC CULTURE MADRASAH ALIYAH LEVEL - Sifa Lutfiyani Atiqoh; Mohamad Ali (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2018)
Textbook is a part of the prominent study resources used by both teacher and student in the teaching and learning process. The latest research’s outcomes that held by PPIM UIN Jakarta in 2016 found that there is some extremism content in senior high school’s Islamic religious textbook. Based on that fact, this research tries to know whether if there are extremism contents in the Madrasah Aliyah’s Islamic religious textbooks published by the ministry of religion or not. In addition, this research wants to know the type of extremist content in the textbook.This research is qualitative research. Based on the way the data were collected, this research called library research. It means that to collect the information or the primer and secondary data, the researcher must examine the documents from the library.The conclusion from this research is there are about six texts that have been indicate including the extremism view in the Madrasah Aliyah Islamic civilization history textbook published by Kemenag. The type of extremist content from those texts is using violent and assassination as a part of carrying out coup d’etat. Those texts interpreted by the book writer as a “brave” attitude and best achievement. Bravery is a positive word, but in this book, this word is used to courage coup d’etat even violent and assassination that we know those behaviour are extremist action. Those findings show that there are extremism contents and it is promoted in the Madrasah Aliyah Islamic civilization history textbook. Those contents are in contradiction with the regulation that produced by the ministry of culture and education (Permendikbud) number 8 the year 2016 about the textbook that used by education units